Chilean Transition to Democracy. the Historical Time of the Plebiscitary Event Between 1987-1988 [Transición Chilena a la Democracia. el Tiempo Histórico del Acontecimiento Plebiscitario Entre 1987-1988.] - Moyano-Barahona, C (Ariadna Ediciones, 2022)
The main objective of this article is to recover the immediate historicity of the categories of "consensus, pact and agreement" during the years 1987-1989, placing special emphasis on three elements: a) the policies of failed alliances; b) the meaning constructed by some intellectuals of the opposition to the military dictatorship and c) the "situated receptions" of the transition processes from other latitudes, particularly that of Spain. With the above, it seeks to investigate the horizons of possibilities of the present-past and through there, rethink the complexities of a time of high uncertainty, forgotten in the present criticisms of the Transition carried out, which decontextualizes the meaning of the substantial categories that guided the imaginary of the process. © 2022 Ariadna Ediciones. All rights reserved.